2001
DOI: 10.1016/s1350-4177(00)00030-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the emission of ‘alkali-metal–noble-gas’ van der Waals molecules from cavitation bubbles

Abstract: Visible emission spectra in the vicinity of resonance lines of alkali metals were recorded from acoustically cavitating aqueous and 1-octanol solutions (acoustic frequency: 20 kHz; solutes: Ar (or Kr), NaCl, RbCl or rubidium 1-octanolate). The maximum intrabubble density deduced from line shift data was approximately 5 +/- 0.7 x 10(26) m-3, i.e. approximately 18 +/- 2 amagats. It is demonstrated that (i) the emission from alkali metals arose from the gas phase of bubbles, (ii) the blue satellite and line disto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
2
39
0
4
Order By: Relevance
“…According to Kordylla et al [21] the nucleation work needed for crystallization is strongly reduced by the presence of a liquid–gas interface (the bubble surface), therefore the presence of the bubble surface accelerates the crystal nucleation. It is worth mentioning that Lepoint-Mullie and co-workers detected visible emission spectra in the vicinity of resonance lines of alkali metals from acoustically cavitating aqueous and 1-octanol solutions of NaCl and RbCl [22]. They showed that the emission from the alkali metals arose from the gas phase of the bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kordylla et al [21] the nucleation work needed for crystallization is strongly reduced by the presence of a liquid–gas interface (the bubble surface), therefore the presence of the bubble surface accelerates the crystal nucleation. It is worth mentioning that Lepoint-Mullie and co-workers detected visible emission spectra in the vicinity of resonance lines of alkali metals from acoustically cavitating aqueous and 1-octanol solutions of NaCl and RbCl [22]. They showed that the emission from the alkali metals arose from the gas phase of the bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…When metal ions are present in the solution being irradiated, emission lines from the excited-state metal atoms are observed in addition to the broad continuum-as reported by a number of researchers working with alkali metal salt solutions. [10][11][12][13][14][15][16][17][18] However, while this is a widely observed phenomenon, the mechanism for the formation of the excited metal atoms and the site where these emission lines originate from are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…The first is where emission is from the gas phase inside the vapour/gaseous core of the collapsing bubbles. [10,12,13,15] As sodium ions are not volatile, this involves the injection of fluid (most likely interfacial material) into the bubble core, followed by subsequent evaporation of the water, leaving bare sodium ions, in a fashion not dissimilar to what takes place in atomic absorption spectroscopy. These ions are then reduced and excited in the gas phase, and eventually relax back to the ground state by light emission.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier it was reported that small amount of surfactant leads to the growth of intensity of Na line, as well as in a case of large concentration of salt [14]. It was also calculated that the thickness of a salt-solution layer of about 16 nm near bubble boundary is enough for explanation of Na line intensity [15]. In the case of surfactant addition a thinner layer is required.…”
Section: Resultsmentioning
confidence: 96%